2003
DOI: 10.1080/0963828031000137081
|View full text |Cite
|
Sign up to set email alerts
|

Measuring participation according to the International Classification of Functioning, Disability and Health (ICF)

Abstract: Eleven survey instruments were identified, of which nine were evaluated on participation. All of the nine instruments measure participation to some extent. The two instruments closest to solely involve items on participation level are the Perceived Handicap Questionnaire (PHQ) and the London Handicap Scale (LHS). The PHQ is measuring the perception of participation. In the LHS, the items are formulated in terms of participation, while the response categories include all components of the ICF, from problems in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
222
2
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(249 citation statements)
references
References 9 publications
(7 reference statements)
11
222
2
11
Order By: Relevance
“…A limitation is that the ICF emphasises that in addition to measuring impairments and function, clinicians should also assess participation (Perenboom and Chorus, 2003;WHO, 2001). Most of the studies included only reported UE impairment outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation is that the ICF emphasises that in addition to measuring impairments and function, clinicians should also assess participation (Perenboom and Chorus, 2003;WHO, 2001). Most of the studies included only reported UE impairment outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…outlined the revision process and discussed the rationale for the ICF and the needs that it serves in rehabilitation. Also reviewed in this special issue were some unique features of this classification system, with articles by Perenboom and Chorus (2003) on the Participation measure, and Schneidert, Hurst, Miller, and Üstün (2003) on the Environmental Factor, among others.Stucki, Ewert, and Cieza (2003) provided a general discussion of the ICF's potential as a functional tool and concluded that the ICF's new language is an exciting landmark for rehabilitation, potentially leading to a stronger position for rehabilitation within the medical community, enhanced multiprofessional communication, and improved communication between patients and rehabilitation professionals. This optimistic view was echoed by Üstün, , whose overview of the development of the ICF and the needs it serves in rehabilitation led them to conclude that it is a needed and essential tool.…”
mentioning
confidence: 99%
“…Se diferentes estratégias de códigos são utilizadas, uma vez que existe uma variabilidade de apreciação dependente do contexto sociocultural, isso coloca dificuldades para a comparação de dados entre os países; assim, alguns países têm desenvolvido distinções pró-prias de atividade e de participação 22,23 .…”
Section: Alguns Dilemas Colocados Para a Incorporação Do Modelo Da Cifunclassified